Performance of NUA45 bean variety between two generations for seeds grown under farmer management at Rupike Irrigation Scheme in Masvingo, Zimbabwe - Benhura, Chakare; Mapanda, Farai; Machisvo, Albert; Mavhiri, D; Chirambadare, Tinashe (International Journal on Food, Agriculture and Natural Resources, 2024)
Among bean legumes, there are recently developed varieties known as nutritionally enhanced beans such as NUA 35 and NUA 45 sugar beans. The objective of the research was to assess the performance of NUA 45 foundation, certified and commodity seeds grown under farmer management at Rupike Irrigation Scheme in Masvingo. Concentrations of zinc (2.75-4.45mg/kg) and iron (70.85-104.5 mg/kg) in the soils were below expected levels of 100 mg/kg and 150 mg/kg respectively.  The NUA 45 sugar bean missed the target potential yield (2400 kg/ha for Highveld) by between 54% and 62%. The 100 seed mass of second generation seeds ranged from 62.13 to 78.47 g. Protein concentration of the seeds which range from 19.79 to 22.86% increased from first generation (F1) to second generation (F2) for each of Foundation, Certified and Commodity seeds. The concentration of fibre with minimum and maximum levels of 5.76% and 8.43 % respectively increased from first generation to second generation for Foundation and Certified seeds. The 95% confidence interval for Zinc concentration at F1 (planted) is 10.84 ≤ µZn≤11.18 mg/kg and also the 95% confidence interval for Zinc concentration at F2 (harvested) is 11.79 ≤ µZn≤12.12 mg/kg and lower than CBI claim of 38.00 mg/Kg. The 95% confidence intervals for iron concentration ranged from 28.50 ≤ µFe≤30.57 mg/kg with the highest being 30.59 ≤ µFe≤32.34 mg/kg are below the CBI claim of 93.00 mg/kg. The nutrients levels increased from the first generation to the second generation of seeds for each of foundation, certified and commodity seeds.